Search for violations of Lorentz invariance and CPT symmetry in Bs^0 mixing. - Cheung, S; Evans, T; Gandini, P; Hadavizadeh, T; Harnew, N; Hill, D; Jalocha, P; John, M; Lupton, O; Malde, S; Nandi, A; Topp-Jorgenson, S; et al. (American Physical Society, 2016)
Violations of CPT symmetry and Lorentz invariance are searched for by studying interference effects in B^0 mixing and in Bs^0 mixing. Samples of B^0 → J/ψKS^0 and Bs^0 → J/ψK^+K^- decays are recorded by the LHCb detector in proton-proton collisions at center-of-mass energies of 7 and 8 TeV, corresponding to an integrated luminosity of 3 fb^-1. No periodic variations of the particle-antiparticle mass differences are found, consistent with Lorentz invariance and CPT symmetry. Results are expressed in terms of the standard model extension parameter Δaμ with precisions of O(10^-15) and O(10^-14)  GeV for the B^0 and Bs^0 systems, respectively. With no assumption on Lorentz (non)invariance, the CPT-violating parameter z in the Bs^0 system is measured for the first time and found to be Re(z) = -0.022 ± 0.033 ± 0.005 and Im(z) = 0.004 ± 0.011 ± 0.002, where the first uncertainties are statistical and the second systematic.